Electromagnetic scattering modelling for quantitative remote sensing - Jin, Ya-Qiu (World Scientific, 1993)
This book is a comprehensive account of the theoretical models and techniques required for a full interpretation of the rich images and data that remote sensing can provide. Starting with the basics of vector radiative transfer and scattering theory, the book goes on to develop quantitative methods involving most comprehensive models of discrete scatters, continuous random media and randomly rough surfaces. References are constantly made to real-world parameters and models involved in the probing of different types of geographical terrain. The book is intended as an introductory graduate text and a research reference. It assumes a reasonable foundation in electromagnetism and common techniques in mathematical physics.